Lentiviral-Mediated Overexpression of the 18 kDa Translocator Protein (TSPO) in the Hippocampal Dentate Gyrus Ameliorates LPS-Induced Cognitive Impairment in Mice - Wang, Wei; Zhang, Liming; Zhang, Xiaoying; Xue, Rui; Li, Lei; Zhao, Weixing; Fu, Qiang; Mi, Weidong; Li, Yunfeng (Frontiers in Pharmacology, 2016)
The 18 kDa translocator protein (TSPO) is involved in the immune/inflammatory response. However, the exact role that TSPO plays in neuroinflammation-induced cognitive impairment is still elusive. The purpose of our present study was to investigate the effects of lentiviral-mediated hippocampal overexpression of the TSPO in a mouse model of LPS-induced cognitive impairment. We established a mouse cognitive impairment model using systematic daily administration of lipopolysaccharide (LPS) (0.5 mg/kg). Microinjection of the dentate gyrus of the mouse with lentiviral vectors, which contained a cDNA targeting TSPO (Lv-TSPO), resulted in a significant increase in TSPO expression and allopregnanolone production. Mice treated with LPS showed cognitive deficits in the novel object recognition test and the Morris water maze test that could be ameliorated by TSPO overexpression. In addition, TSPO overexpression reversed LPS-induced microglial activation and accumulation of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α. Moreover, TSPO overexpression attenuated the LPS-induced impairment of hippocampal neurogenesis. Our results suggest that local overexpression of TSPO in the hippocampal dentate gyrus alleviated LPS-induced cognitive deficits, and its effects might be mediated by the attenuation of inflammatory cytokines, inhibition of microglial activation, and promotion of neurogenesis.